MY COMPUTER SKILLS:STRENGTHS AND WEAKNESSES (Ustozlar uchun, 2026)
This article provides a reflective analysis of personal computer skills, focusing on the author’s strengths and weaknesses in using digital technologies. The study explores key areas such as typing, software proficiency, internet navigation, and problem-solving abilities. While strengths include basic office applications and online communication, weaknesses involve programming, data analysis, and advanced system maintenance. The article emphasizes the importance of continuous learning and self-assessment in developing computer literacy.